An eco‑epidemiological model for malaria with Microsporidia MB as bio‑control agent - Mfangnia, C.N.T.; Tonnang, H.E.Z.; Tsanou, B.; Herren, J.K. (2025)
Microsporidia MB is an endosymbiont which naturally infects Anopheles mosquitoes. Due to its ability to block Plasmodium transmission, it shows potential as a bio-based agent for the control of malaria. Its self-sustainability is promising, as it can spread through both vertical and horizontal transmissions. However, its low prevalence in mosquito populations remains a challenge. We develop an eco-epidemiological mathematical model describing the co-dynamics of Microsporidia MB (within mosquito population) and malaria (within human population). The model is used to assess the potential of Microsporidia MB-infected mosquitoes on the control of malaria infection. The results on the basic reproduction numbers, the stability of the equilibria, and the existence of bifurcations are obtained, providing conditions for the extinction and persistence of MB-infected mosquitoes. We highlight relevant threshold parameters for the elimination and persistence of MB-infected mosquitoes and malaria-infected individuals. Using real data from Kenya, we found that, given a horizontal transmission rate between 0 and 0.5, a minimum vertical rate of 0.55 is required to avoid extinction of MB-infected mosquitoes. The predicted prevalence of MB-infected mosquitoes using transmission rates reported from lab experiments align with the observed low prevalence of MB-infected mosquitoes in the field, thereby validating our model and results. Finally, predictions indicate that increasing MB mosquito infection could effectively control malaria, with target prevalence varying by region: 15% in Highland, 40% on the coast, and 70% in the Lake region. This study offers insights into the use of bio-based vector population replacement solutions to reduce malaria incidence in regions where Microsporidia MB is prevalent.